4-Methoxycarbonyl Curcumin: A Unique Inhibitor of Both Inflammatory Mediators and Periodontal Inflammation. (24th December 2013) - Gu, Ying; Lee, Hsi-Ming; Napolitano, Nicole; Clemens, McKenzie; Zhang, Yazhou; Sorsa, Timo; Zhang, Yu; Johnson, Francis; Golub, Lorne M.
Abstract : Chronic inflammatory diseases such as periodontitis have been associated with increased risk for various medical conditions including diabetes and cardiovascular disease. Endotoxin (lipopolysaccharide, LPS), derived from gram-negative periodonto-pathogens, can induce the local accumulation of mononuclear cells in the inflammatory lesion, increasing proinflammatory cytokines and matrix metalloproteinases (MMPs). This ultimately results in the destruction of periodontal connective tissues including alveolar bone. Curcumin is the principal dyestuff in the popular Indian spice turmeric and has significant regulatory effects on inflammatory mediators but is characterized by poor solubility and low bioactivity. Recently, we developed a series of chemically modified curcumins (CMCs) with increased solubility and zinc-binding activity, while retaining, or further enhancing, their therapeutic effects. In the current study, we demonstrate that a novel CMC (CMC 2.5: 4-methoxycarbonyl curcumin) has significant inhibitory effects, better than the parent compound curcumin, on proinflammatory cytokines and MMPs in in vitro, in cell culture, and in an animal model of periodontal inflammation. The therapeutic potential of CMC 2.5 and its congeners may help to prevent tissue damage during various chronic inflammatory diseases including periodontitis and may reduce the risks of systemic diseases associated with this local disorder.